Growth of manglid (Manglietia glauca Bl.) from three provenances until age 4.5 years at Candiroto Temanggung Central Java. Issue 1 (November 2021) - Pudjiono, S; Mashudi,; Susanto, M; Baskorowati, L; Setiadi, D; Sulaeman, M; Hartati, R A; Wibowo, A
Abstract: This study was carried to examine the best provenance of seed source of Manglietia glauca at 4.5 years old. The study was conducted in Candiroto, Temanggung, Central Java. A Randomized Complete Block Design with three provenances consisting of 15 parent trees from Tasikmalaya, ten parent trees from Sumedang, and 75 parent trees from Sukabumi, West Java, were divided into ten replications. Each replication has 100 plots, and each plot consists of four plants with a planting distance is 4 m x 3m. The plant characteristics, including height and stem diameter, were measured at the age of 0.5, 1.5, 2.5, 3.5 and 4.5 years. Variant analysis and Duncan Multiple Range Test in each measurement stage were performed. The significant differences of plant height among provenances were found from 0.5 to 3.5 years old and were not significantly different afterward. The stem diameter differs significantly among the provenances at 1.5 years old only; afterward, they were not significantly different. The average plant height and stem diameter at 4.5 years old were between 864-917 cm and 12.34-12.48 cm, and they were not significantly different. Therefore, it is possible to choose any seed sources of the three provenances of manglid to be used for plantation.